Study time within pre-registration nurse education: A critical review of the literature. (June 2016) - Barker, Caroline; King, Nigel; Snowden, Michael; Ousey, Karen
Summary: Background: Pre-registration nursing students throughout the United Kingdom (UK) are required to complete a minimum number of theory hours within the course. Anecdotal evidence suggests that students are required to attend campus for approximately fifty percent of the theory hours. The remaining theory hours are often labelled as 'study time' in which students are not required to attend campus. There is a general assumption amongst many academics that all students are prepared and motivated to direct their learning and therefore use this time to study. However some students chose to work during this time and many have dependents. Considering the increasing cost of nurse education combined with the government cuts to student bursaries in England it is timely to review the literature to determine how study time is used within pre-registration nurse education. Objective: To present a critical review of the literature pertaining to study time in pre-registration nurse education. Design: An integrative review of the literature. Data Sources: A search of electronic databases: Cumulative Index to Nursing and Allied Health (CINAHL); Cochrane; Medline; Science Direct; Blackwell Synergy; Electronic Journals Service (EJS); Scopus; Taylor & Francis, Eric and Routledge Wiley was undertaken. Review Methods: The inclusion criteria consisted of peer reviewed primary research, discussion papers, unpublished doctoral theses' and editorial papers directly related to the key words and nurse education published in English. Results: Twelve papers were included in the review. Analysis of the papers led to the development of two themes: orientation to self-directed learning (SDL) and preparation for SDL. Conclusions: The literature demonstrates that pre-registration nursing students lack the necessary skills for SDL. There is a lack of research on how study time is used within pre-registration nurse education. This calls for empirical research to fully explore how nursing students and lecturers perceive study time within pre-registration nursing curricula. Highlights: Research on the use of directed study time within pre-registration nurse education is lacking. Nursing students prefer others to direct their learning. Many nursing students lack the skills required for self-directed learning. Further research is needed to explore the use of directed study time within pre-registration nurse education.